Determination of The Success of Muslim Women Ebtrepreneurs: The Conceptual Model - Bahri, Efri Syamsul; Wibowo, Hendro; Wiharjo, Suyadi Murdi (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2022)
Khadijah has set an example as a successful Muslim woman entrepreneur. However, specific research focusing on the success of Muslim female entrepreneurs is still limited. This study aims to identify the determinants of the success of Muslim women entrepreneurs and develop a conceptual model. Literature research data sourced from Google Scholar. Data collection using the publish or perish application. Data analysis used the preferred reporting items for systematic reviews and meta-analyses (PRISMA) approach. The study's results have identified four indicators of success for Muslim women entrepreneurs: business performance, business viability, staying in the industry for the long term, and generating profits. Furthermore, there are four dimensions of the success factors of Muslim women entrepreneurs: attitude, motivation, competency, and resources. In the end, this research has also produced a conceptual model for determining the success of Muslim women entrepreneurs. Therefore, the ministry in charge of entrepreneurship can respond to the results of this study by increasing the contribution to the four success factors of Muslim women entrepreneurs.Khadijah has set an example as a successful Muslim woman entrepreneur. However, specific research focusing on the success of Muslim female entrepreneurs is still limited. This study aims to identify the determinants of the success of Muslim women entrepreneurs and develop a conceptual model. Literature research data sourced from Google Scholar. Data collection using the publish or perish application. Data analysis used the preferred reporting items for systematic reviews and meta-analyses (PRISMA) approach. The study's results have identified four indicators of success for Muslim women entrepreneurs: business performance, business viability, staying in the industry for the long term, and generating profits. Furthermore, there are four dimensions of the success factors of Muslim women entrepreneurs: attitude, motivation, competency, and resources. In the end, this research has also produced a conceptual model for determining the success of Muslim women entrepreneurs. Therefore, the ministry in charge of entrepreneurship can respond to the results of this study by increasing the contribution to the four success factors of Muslim women entrepreneurs